Optimizing the Money Demand Function in Islamic States with Insights from Milton Friedman - Yuda Septia Fitri; Vemy Suci Asih; Dudang Gojali (UIN Sunan Gunung Djati Bandung, 2024)
This study aims to develop a comprehensive model of money demand in Muslim countries. The methodology employed is a combination of qualitative and quantitative methods. The qualitative approach involves an extensive literature review of microeconomic theory, particularly the theory of marginal utility, Muslim consumption patterns, and macroeconomic theory regarding the factors influencing money demand. These theories help construct a robust model of money demand in an Islamic context. The quantitative approach verifies the proposed model using multiple linear regression analysis. This analysis examines the relationship between money supply, GDP, the rate of return on sukuk, and the collection of zakat, infaq, and charity in Indonesia over a period of 10 years. Key elements of the model include the integration of Islamic financial principles such as zakat, infaq, and charity, which are shown to have a positive relationship with the demand for money. The significance of using a mix of qualitative and quantitative methods lies in the ability to build a theoretical framework grounded in Islamic economic principles and empirically validate it with real-world data. The qualitative aspect provides a deep understanding of the specific theories and literature, including the works on marginal utility and Muslim consumption behaviors, which are crucial for modeling money demand in Islamic economies. The study findings are particularly important as they reveal a positive relationship between the collection of zakat, infaq, and charity, and the demand for money. This suggests that these Islamic financial instruments play a significant role in shaping money demand, highlighting the unique dynamics of Islamic economies. By integrating these elements, the study provides valuable insights into the financial behaviors in Muslim countries and underscores the importance of incorporating Islamic principles in economic models. This research contributes to a better understanding of how Islamic financial practices influence economic stability and growth, offering a pathway for developing effective monetary policies in Muslim countries.